Risk Factor and Management of Peritonitis related to Peritoneal Dialysis in Low Income Countries - Setiawan Nathan, Daniel; Sanjaya, Charles (The International Journal of Medical Science and Health Research, 2024)
Background: Peritoneal dyalisis (PD) may offer some advantages over hemodyalisis (HD) with regard to quality of life and kidney transplantation outcome and costs savings. Methods: This systematic review focused on full-text English literature published between 2014 and 2024 using the PRISMA 2020 guidelines. Editorials and review pieces published in the same journal as the submission without a DOI were not accepted. The literature was compiled using PubMed, ScienceDirect, and SagePub, among other online venues. Result: Five publications were found to be directly related to our ongoing systematic examination after a rigorous three-level screening approach. Subsequently, a comprehensive analysis of the complete text was conducted, and additional scrutiny was given to these articles. Conclusion: The technologies lead to a decrease in the peritonitis rates but effective training of the patient about catheter care and PD techniques still play an important role in the prevention of PD peritonitis.